Finite element analysis of an anchored reinforced earth wall under slope surcharge - Ali, F.; Bhuiyan, M.Z.I.; Hai, L.C. (2010)
A parametric study was conducted using a finite element method to investigate the performance of an instrumented reinforced anchored earth wall. The performances was characterized herein under two criteria namely stress and deformation criteria. This study revealed that the increase in slope height and gradient of surcharge significantly enhance the summation of maximum axial stress in the reinforcing bars. However, the influence of surcharge becomes negligible when the surcharge height goes beyond 1.5 times the height of the wall. The influence of slope setback decreases with increase in setback but beyond 1.5 times the block width becomes insignificant